2014
DOI: 10.1007/s00381-014-2424-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of posterior fossa decompression with or without duraplasty in children with Type I Chiari malformation

Abstract: Purpose Chiari Malformation Type I (CM1) is a common and often debilitating neurosurgical disease. Whether to treat CM1 patients with a traditional posterior fossa decompression with duraplasty (PFDD) or a less invasive extradural decompression (PFDO) is controversial. The purpose of this study was to compare clinical outcome and syrinx resolution between the two procedures. Methods We retrospectively reviewed the records of 36 patients treated with PFDD and 29 patients with PFDO between 2003 and 2011. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 27 publications
(56 reference statements)
4
46
0
3
Order By: Relevance
“…The authors recommended the more invasive PFDD as first-line treatment for more severe patients with rapidly progressive symptoms or severe neurological deficits. 16 Our data echoes these results in that even though there was no difference with overall clinical outcome between the 2 techniques, patient who underwent dural splitting had a quicker and easier recovery.…”
Section: Discussionsupporting
confidence: 80%
“…The authors recommended the more invasive PFDD as first-line treatment for more severe patients with rapidly progressive symptoms or severe neurological deficits. 16 Our data echoes these results in that even though there was no difference with overall clinical outcome between the 2 techniques, patient who underwent dural splitting had a quicker and easier recovery.…”
Section: Discussionsupporting
confidence: 80%
“…It was found that 60.1% of all CM-1 were managed with PFD, which is consistent with the current trend favoring conservative surgical management based on the theoretical advantages of this less invasive approach [2,3]. Recent studies further support this argument and have shown that PFD produces comparable rates of clinical and radiological improvements in CM-1 patients without syringomyelia [4,5]. Additionally, the national data set indicates that recent trends have less likely favored an upper cervical laminectomy with PFD than with PFDD (41.7 vs. 49.1%, p = 0.03).…”
Section: Discussionsupporting
confidence: 71%
“…We decided to use the CCOS as the primary clinical outcome score as it provides a more objective comparison of clinical outcome than other Gestalt methods [22,23] . Our results support the previous findings of Lee et al [24] that the clinical outcome in children with CM1, as judged by CCOS, did not differ between patients who had undergone duroplasty versus extradural decompression only.…”
Section: Discussionsupporting
confidence: 83%
“…To our knowledge, this is the first report of this in the literature. A few studies have compared the results of 2 procedures for CM1 in children, particularly BD only versus BD and DOPD [18,20,24] ; however, all but one of these reports share an important limitation, i.e., they lack a standardized and validated method to assess the clinical outcome [24] . We decided to use the CCOS as the primary clinical outcome score as it provides a more objective comparison of clinical outcome than other Gestalt methods [22,23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation